Implementasi Algoritma Naïve Bayes Berbasis Particle Swarm Optimization Untuk Memprediksi Penyakit Hepatitis - Husniah, Hilda Farida; Arifin, Toni (Jurnal Ilmu Komputer, 2021)
Hepatitis disease is an inflammatory disease of the liver cells, caused by infections (viruses, bacteria, parasites), medicines (including traditional medicines), consuming alcohol, excessive fats and autoimmune diseases. The cause of hepatitis is often caused by Hepatitis B and C Virus. The Hepatitis prevalence in Indonesia in 2013 amounted to 1.2% increased twice compared to the year 2007 Riskesdas of 0.6%. East Nusa Tenggara is the province with the highest prevalence of Hepatitis in 2013 of 4.3%. Researchers are trying to make a breakthrough by making research for the prediction classification of Hepatitis patients with data mining technique. Naïve Bayes is a method used to predict the probability of the future based on past experience and proved to have a high level of accuracy and high speed of calculation. Particle Swarm Optimization is used to improve the accuracy of the method. The research aims to determine if the Naïve Bayes-based Particle Swarm Optimization method can improve the accuracy of the good. The results of using Naïve Bayes-based Particle Swarm Optimization has a confusion matrix accuracy of 91.90% and an AUC of 0946 proved that has good results than Naïve Bayes has a confusion matrix accuracy of 88.52% and AUC 0896.